Efficient recycling of organic wastes in arecanut (Areca catechu) and cocoa (Theobroma cacao) plantation through vermicomposting - CHOWDAPPA, P; BIDDAPPA, C C; SUJATHA, S (The Indian Journal of Agricultural Sciences, 2013)
The possibility of converting available organic wastes in arecanut (Areca catechu L.) and cocoa (Theobroma cacao L.) gardens into vennicompost by using African night crawler (Eudrilus eugeniae) was studied during 1994-95. The result indicated that the organic wastes could be efficiently converted into vermicompost with a recovery of 74.65-87.75 % in a composting period of 3 months. Earthworm biomass doubled irrespective of organic waste used in a period of two months. Major nutrient (NPK) and micronutrient (Cu, Zn, Fe and Mn ) contents were slightly higher in all the vermicompost samples than in normal compost. Vermicompost had lower C:N ratio and pH than normal compost irrespective of the source of organic waste. Microbial population was considerably higher in vermicompost than in normal compost. Economics of vermicompost production revealed that the profit of Rs 1.51-1.69 could be realized from 1 kg of the compost. Estimated cost of commercial vermicompost production showed that a profit of Rs 11 114/could be obtained from the vermicompost production from organic wastes available in 1 hectarc of arecanut plantation.